ONO REGO ONO RUPO: EFEK PLASEBO HARGA DAN KONSUMSI HEDONIS DI MAL KOTA YOGYAKARTA - Faizal Ardiyanto (Jurnal Manajemen, 2018)
There are interesting phenomena related to consumer behavior in Yogyakarta. One of them is price placebo effect. In Javanese language can be found words in relevance with price placebo effect, that is ”ono rego ono rupo” which can be translated to where there is price, there is quality. Therefore, this research is aimed to prove the influence of price placebo effect on brand equity and hedonic consumption, atmospheric cues on hedonic consumption, and also the influence of hedonic consumption on brand equity and impulsive buying behavior. Path analysis is used to test the hypotheses and the total of 506 respondents are participated in this research. The result indicated that all of this research hypotheses are supported.